2021
DOI: 10.53562/ajcb.ndzf2600
|View full text |Cite
|
Sign up to set email alerts
|

Butterflies (Lepidoptera: Rhopalocera) in and around the Unakoti Archaeological Site with 59 new additions to the Butterfly Fauna of Tripura, North-eastern India

Abstract: The authors have surveyed different habitats in and around the Unakoti Archaeological Site and documented a total of 216 species classified under 6 families, 23 subfamilies and 126 genera of the order Lepidoptera. The study was conducted from 2016 to 2020, covering different seasons namely pre-monsoon (Jan-Apr), monsoon (May-Aug) and post-monsoon (Sep-Dec) respectively. The study reports 2 species under schedule I, 25 species under schedule II, and 5 species under schedule IV of the Indian Wildlife (Protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The pattern of high diversity, richness and similarity during pre-monsoon (summer) and post-monsoon (autumn) seasons in the study area is in concordance with previous findings on butterfly seasonality from the regions experiencing tropical to sub-tropical type of climate in India (Kunte, 1997;Padhye et al, 2006;Sengupta et al, 2014;Gupta et al, 2019;Arya et al, 2020a;Sharmila et al, 2020;Bhowmik and Chowdhury, 2021). In tropical regions, annual patterns of precipitation have a significant impact on butterfly communities (Valtonen et al, 2013), and the occurrence of dry-wet seasonal cycles influence the host plant dynamics and generate bi-annual rhythms in species diversity and similarity of butterfly communities (Grøtan et al, 2012(Grøtan et al, , 2014.…”
Section: Discussionsupporting
confidence: 91%
“…The pattern of high diversity, richness and similarity during pre-monsoon (summer) and post-monsoon (autumn) seasons in the study area is in concordance with previous findings on butterfly seasonality from the regions experiencing tropical to sub-tropical type of climate in India (Kunte, 1997;Padhye et al, 2006;Sengupta et al, 2014;Gupta et al, 2019;Arya et al, 2020a;Sharmila et al, 2020;Bhowmik and Chowdhury, 2021). In tropical regions, annual patterns of precipitation have a significant impact on butterfly communities (Valtonen et al, 2013), and the occurrence of dry-wet seasonal cycles influence the host plant dynamics and generate bi-annual rhythms in species diversity and similarity of butterfly communities (Grøtan et al, 2012(Grøtan et al, , 2014.…”
Section: Discussionsupporting
confidence: 91%
“…These species include Troides spp., H. epicles, Symbrenthia spp. and Euthalia malaccana (Fruhstorfer, 1899), and Dichorragia nesimachus (Boisduval, 1836) (Saha and Das 2012; Mehra et al 2018;Bhowmik and Chowdhury 2021;Peggie et al 2021). The result showed that butterflies could be bioindicators either in terms of the diversity of environmental characteristics (abundance and vegetation diversity) or sensitivity to environmental conditions (temperature, humidity, light intensity, wind speed, as well as the presence of pollutants) (Ghazanfar et al 2016;Comay et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We will be using the name Vagrans egista sinha (Kollar, [1844]), which is the most widely adopted name in circulation . (Sondhi & Kunte, 2016) to rare (Bhowmik & Chowdhury, 2021), depending on the location. In India, this species is reported in tropical deciduous forests within 400-1400 m above sea level and Shorea robusta forests below 1000 m asl, and habitat-wise, they are found within riverine habitat, village homes near forest edges, and gardens (Smetacek, 2012;Sondhi & Kunte, 2018;Bhowmik & Chowdhury, 2021).…”
Section: Introductionmentioning
confidence: 99%